Case Report: Magic Mushroom (Psilocybe cubensis) Intoxication - Andrian Fajar Kusumadewi (HM Publisher, 2020)
Psilocybe mushroom, or widely known as the magic mushroom is a variety of mushroom commonly consumed because of hallucinogenic traits it causes toward its consumer. This hallucinogenic effect is caused by Psilocybin, a hallucinogenic substance often found within Psilocybe mushroom. This substance affects mental state of the consumer and has similar effect to those of LSD and Mescaline. Aside from its effect to cause mental disturbance, consumption of this mushroom may cause acute renal injury which leads to a fatal and life-threatening situation. A case of Psilocybe intoxication had been reported in a 22 years old male with a confirmed history of consuming Psilocybe mushroom. Patient first came with a symptom of disorientation and restlessness. Patient also often shook his head off, laughed out, screamed, and continuously making bizarre movements. Psychiatric examination confirmed a sign of auditory hallucination, unstable mood, and stereotypical behavior experienced by the patient. This case report was intended to elaborate the effects of Psilocybe mushroom consumption against physical and mental condition of the consumer, and its management in clinical settings.